Preparation and Characterization of Iron Oxide Nanoparticles-Reduced Graphene Oxide Composites (IO-RGO) and Studying Some of its Medical Applications - Bdewi , Shahbaa f.; Mohammed , Yusra A.; Jubair , Ahmed M; Meteab , Hussein Hatam (Journal of Science in Medicine and Life, 2024)
A method of preparing iron oxide nanoparticles is green synthesis, in which pomegranate syrup extract is used in the synistation of the nanoparticles. In extracts of fruit quantities of pomegranate syrup, there may be some phytochemical substances such as polyphenols, flavonoids and organic acids that may act both as reducing and stabilizing reagents for the preparation of nanoparticles. Iron oxide nanoparticles was synthesized in the present research work by Sol – Gel auto-combustion technique some of these approaches and chemicals used are almost green and cost effective than the other methods of synthesis self combustion process has been ignited by natural extract of pomegranate Iraqi plant. and then to composite with reduced graphene oxide. Characterization of the prepared powder compositions was done throughPowder X-ray Diffraction [XRD] and Scanning Electron Microscopy [SEM].